TANNIC ACID SUPPORTED BY MAGNETITE NANOPARTICLES FOR THE REMOVAL OF CdII AND PbII FROM WATER - Camilo Eduardo García Henao; Guillermo Salamanca Grosso; Anderson Guarnizo Franco (Química Nova)
In recent decades, increasing concerns about heavy metal contamination in wastewater and the high costs associated with conventional removal methods have driven the search for greener and more cost-effective adsorbents. In this study, we focused on a hybrid composed of tannic acid (TA) and magnetite nanoparticles (Fe3O4@TA) as an alternative for removing CdII and PbII from aqueous solutions. Characterization techniques, including transmission electron microscopy (TEM), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI TOF-MS), and Fourier transform infrared spectroscopy (FTIR), were employed to confirm the nanometric nature of the composite and its organic-inorganic composition. Several adsorption parameters, such as pH, contact time, adsorption kinetics, and initial ion concentration, were evaluated. Sorption kinetic data were best described by the pseudo-second order kinetic model, providing equilibrium rate constants (k2) of 0.0194 g mg-1 min-1 for CdII and 0.0134 mg-1 min-1 for PbII. Furthermore, the adsorption isotherms for the Fe3O4@TA adsorbent exhibited a better fit to the Freundlich isotherm model compared to the Langmuir isotherm model. This nanocomposite holds promise as a sustainable and economical solution for heavy metal removal from wastewater.